Application of Volatile Organic Compound Analysis in a Nutritional Intervention Study: Differential Responses during Five Hours Following Consumption of a High‐ and a Low‐Fat Dairy Drink. Issue 20 (5th August 2019) - Hageman, Jeske H. J.; Nieuwenhuizen, Arie G.; van Ruth, Saskia M.; Hageman, Jos A.; Keijer, Jaap
Abstract : Scope: Exhaled volatile organic compounds (VOCs) are a possible relevant target for noninvasive assessment of metabolic responses. Using a breathomics approach, it is aimed to explore whether lipid intake influences VOC profiles in exhaled air, and to obtain insight in intra‐ and interindividual variations. Methods and results: Three human interventions are performed. In the first, 12 males consume a high‐fat drink on three study days. In the second, 12 males receive a high‐ and a low‐fat drink on 6 days. In the third, three volunteers consume the high‐fat drink again for tentative compound identification. Participants are asked to exhale, for 5 h postprandial with 15–20 min intervals, into a proton‐transfer‐reaction mass spectrometer, and VOCs in exhaled air are measured. Consumption of a drink alters the VOC profile, with considerable interindividual variation and quantitative intraindividual differences between days. Consumption of two different drinks results in a distinct VOC profile, caused by several specific m / z values. Most of these compounds are identified as being related to ketone body formation and lipid oxidation, showing an increase in high‐ versus low‐fat drink. Conclusion: Exhaled VOCs have the potential to assess differences in metabolic responses induced by nutrition, especially when day‐to‐day variation can be minimized. Abstract : Exhaled air contains volatile organic compounds (VOCs), which are partly derived from the body's internal metabolism. It is shown that differences in VOC profiles can be identified after consumption of dairy drinks differing in amount of lipids. This indicates that analysis of exhaled VOCs may be a useful method to study metabolic effects of nutrition.